Combined Effect of Vajigandhadi Gana Kashaya and Kolakulathadi Churnam in the Management of Janu Sandhigata Vata w.s.r. to Osteoarthritis of Knee Joint (AYUSHDHARA, 2022)
Sandhigata vata is one of such disease commonly affecting a large number of individuals occurs usually after midlife stage. Sandhigata vata can be compared with osteoarthritis of contemporary medical science. In this study, the combined efficacy of Vajigandhadi gana Kashaya churna and Kolakulathadi churna as Lepam in Janu Sandhigata vata having properties like Ushna virya, Vatahara, Ama pachana, Sothahara, Shulahara and Vedana sthapana was evaluated. The textual reference for Vajigandhadi gana is only present but in this study the Gana is prepared in the form of Kwath churna. Kolakulathadi churna was used as external application in the study. The study was designed for the improvement of the cardinal symptoms of Janu Sandhigata vata among the ageing population and marked improvement was noticed. Aim: To study the efficacy of Vajigandhadi gana Kashaya and Kolakulathadilepam in the management of Janu sandhigata vata w.s.r. Osteoarthritis of knee joint. Materials and Methods: 40 patients fulfilling the inclusion criteria after signing the informed consent form were selected from the OPD and IPD of SJSACH. It is a single arm prospective open randomized clinical study. Patients were administered with 50ml of Vajigandhadi gana Kashaya morning and evening after food for 21 days and Kolakulathadi churna as Lepam (external application) over the affected knee joint for 07 days with two assessments on 8th day and 22nd day & follow up after one month. Results: Subjective parameters were assessed using Friedman’s test and Wilcoxon signed rank test and objective parameters were assessed using Paired sample t test. All the parameters had highly significant and significant results with p value. Conclusion: The combined effect of Vajigandhadi gana Kashaya and Kolakulathadilepam was very effective in the management of Janu sandhigata vata (osteoarthritis of knee joint) as most of the drugs in both the formulations possess properties such as Shula hara, Shotha hara, Vedana sthapana, Ama pachana, Balya and Rasayana.